Determinants and indicators of successful aging as a multidimensional outcome: a systematic review of longitudinal studies - Rodrigues, Caue Egea; Grandt, Caine Lucas; Alwafa, Reem Abu; Badrasawi, Manal; Aleksandrova, Krasimira (Frontiers in Public Health, 2023)
Background Successful aging (SA) has been coined as a term to describe the multidimensional aspects associated with achieving optimal combination of physical and mental health along with social well-being health, mental and social well-being at older age. In recent years there has been an increased interest in understanding the role of determinants of SA, such as demographic, biological, behavioral, psychological and social factors. To synthesize the recent evidence, we conducted a systematic review of longitudinal studies on a range of determinants and indicators of SA defined as a multidimensional outcome. Methods A systematic search of PubMed, MEDLINE and Web of Science for finding eligible papers published between August 2016 and June 2023 was conducted following the Preferred Reporting Items for a Systematic Review and Meta-Analysis (PRISMA) guidelines. The review protocol was registered in PROSPERO International Prospective Register of Systematic Reviews (Registration number: CRD42021250200). The web-based automated screening tool–Rayyan–was used for title and abstract screening. The study quality was assessed using the Quality in Prognosis Studies (QUIPS) tool. Results A total of 3,191 records were initially identified using the predefined search strategy. Out of 289 articles selected for full text screening, 22 were found eligible and included in the review. A variety of factors have been explored in relation to SA, ranging from socio-demographic factors, nutrition, lifestyle, biological pathways, psychological health, and well-being. Overall, the results of recent studies have confirmed the role of metabolic health, adherence to healthy dietary patterns, such as the Mediterranean diet, physical activity, non-smoking, and higher socio-economic status as main factors associated with higher odds for SA. Emerging research highlights the role of psycho-social factors and early life health as determinants of SA. Conclusion In summary, this review highlights the importance of healthy living and monitoring metabolic risk along with sustaining psychological well-being in adult life as major determinants of SA. Further methodological and research work on SA would pave the way toward development of adequate health promotion policies in aging societies. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021250200, CRD42021250200.